Morphology and nutritive value of perennial ryegrass cultivars at different phenological stages. (31st July 2019) - Chen, Ao; Bryant, Racheal H.; Edwards, Grant R.
Abstract: Eight perennial ryegrass cultivars (representing the variations in ploidy, heading date and water‐soluble carbohydrates concentration) were investigated for morphology and nutritive value at three phenological stages: pre‐heading vegetative, reproductive and post‐flowering vegetative stages. Chemical compositions and digestibility of morphological components (lamina, pseudostem and reproductive stem) from each perennial ryegrass cultivar were analysed in a split‐plot design. At the vegetative stages, perennial ryegrass cultivars differed significantly in the proportions of lamina and pseudostem. Tetraploid cultivars, Base and Bealey, always had the greatest lamina proportion (51.8% and 53.2% at the pre‐heading and post‐flowering vegetative stages respectively). At the reproductive stage, the emergence of seed heads diminished the differences in morphology among cultivars. Perennial ryegrass cultivars also had distinct nutritive value throughout three phenological stages. The high‐sugar cultivar, AberMagic, had high WSC concentrations (276, 227 and 90 g/kg DM at the pre‐heading vegetative, reproductive and post‐flowering vegetative stages respectively); the intermediate‐heading cultivars, Kamo and Commando, generally had a lower organic matter digestibility in dry matter than the late‐heading cultivars at the pre‐heading vegetative (70.7% vs. 74.4%) and reproductive stage (63.9% vs. 68.2%). However, although the morphological components were different in nutritive value consistently, the differences in morphology did not account for the variation in nutritive value among perennial ryegrass cultivars.